Determination of Optimum Dividend Policy: Empirical Evidence from Listed Firms at the Nairobi Securities Exchange (NSE) 2000- 2010 - Bulla , Dennis (African Journal of Education,Science and Technology (AJEST), 2025)
Dividend decisions remain to be one of the most controversial subjects in corporate finance since the debate on its relevance was started by Lintner in the 1950s. Facts show that, while companies would prefer to pay dividends, they are more concerned with stability and growth of payout. Consequently, this study applied a simple linear regression model to determine stability of dividends for listed firms at the Nairobi Stock Exchange. The parameters estimated are adjustment rate and target payout ratio. Study objectives are: i) to determine the target dividend rate and adjustment rate for the market based on empirical data of listed companies for the period 2000-2010. ii) To determine the relationship between earnings and dividend policy of listed firms at the exchange. Empirical data of 40 listed companies at the Nairobi Securities Exchange was collected and analyzed statistically using a simple regression model (OLS) at the 5% level of significance for the period. Results of analysis from the empirical panel data indicate that overall, listed companies within the period had an average target payout rate of 3.5% of the changes in current earnings and an adjustment rate of 52%. The relationship between current earnings and dividend payout was positive and fairly strong (0.65) and was also statistically significant. Therefore data did not sufficiently justify dividend smoothing at the NSE. Optimum dividend policy for listed firms at the NSE is therefore determined by low target rate and moderately high adjustment rate. Consequently dividend payout is low and fairly unstable creating some uncertainty. Current earnings explained 42% of the variation in dividend payment from the sampled data.